Temporal heterogeneity of prokaryotic micro-organism communities in sediment of traditional freshwater cultured fish ponds in Southwest China. Issue 1 (2nd January 2018) - Zhang, Qing; Tan, Xiao; Lin, Kai; Zeng, Lin; Xiang, Wenliang; Tang, Jie
ABSTRACT: The temporal heterogeneity of prokaryotic microorganism communities in sediment of traditional freshwater cultured fish ponds in Southwest China were investigated by 16S rRNA clone libraries. The result indicated that a total of 47 archaea clones and 392 bacterial clones were recovered from three samples, among them, the bacteria Mitsuaria chitosanitabida, Prolixibacter bellariivorans and Flavihumibacter petaseus and archaea Methanoregula formicica were dominant in the cultivation 1 year (Y1) sample, the bacteria Cetobacterium somerae, Allochromatium vinosum and Rhabdochromatium marinum and archaea Methanolinea tarda were dominant in the cultivation 2 years (Y2) sample, the bacteria Cetobacterium somerae and Bacteroides fragilis and archaea Methanolinea tarda were dominant in the cultivation 4 years (Y4) sample. The Shannon–Wiener ( H ) diversity index and the Simpson dominancy index respectively varied from 2.23 to 2.37 and from 7.30 to 9.04 for three gene libraries. Maximum operational taxonomic unit (OTU) richness was respectively estimated with two different models SChao1 and SACE, and it revealed SChao1 15 and SACE 15 for Y1, SChao1 15.25 and SACE 15 for Y2, SChao1 12 and SACE 12 for Y4. However, the B. fragilis which was found in the Y4 sample was 99% similar to the human and animal pathogen B. fragilis . No pathogenic organisms related to humans or animals were found at any other sample. Mentionable, the more detailed information about the safety of fish pond cultivation environment should receive more attention and further studies.